Effect of Donepezil on Group II mGlu Receptor Agonist- or Antagonist-Induced Amnesia on Passive Avoidance in Mice. Issue 4 (2003) - Sato, Tomoaki; Tanaka, Koh-ichi; Ohnishi, Yoshiko; Irifune, Masahiro; Nishikawa, Takashige
Abstract : We examined the effect of the acetylcholinesterase (ACHE) inhibitor, donepezil hydrocloride (DONP), on group II metabotropic glutamate (mGlu) receptor agonist- or antagonist-induced amnesia in the step-through passive avoidance task in male mice. DCG-IV, a group II mGlu receptor agonist, at dose of 50 ng and LY341495, a group II mGlu receptor antagonist, at dose of 300 ng, significantly attenuated the latency on the step-through task. The subcutaneous injection of DONP at dose of 1 mg/kg 1 hour before passive avoidance performance ameliorated the amnesia induced by DCG-IV and LY341495, whereas donepezil alone did not affect task latency. The results suggest that activation of group II mGlu receptors and disinhibition of the cAMP/PKA signaling pathway (caused by group II mGlu receptor antagonist) have a negative action on step-through passive avoidance memory performance, and that group II mGlu receptors and ACh interact to modulate learning and memory function.